ChemInform Abstract: From an Icosahedron to a Plane: Flattening Dodecaiodo‐dodecaborate by Successive Stripping of Iodine. Issue 3 (22nd January 2013) - Farras, Pau; Vankova, Nina; Zeonjuk, Lei Liu; Warneke, Jonas; Duelcks, Thomas; Heine, Thomas; Vinas, Clara; Teixidor, Francesc; Gabel, Detlef
Abstract Electrospray ionization‐ion‐trap mass spectrometry shows that B2I122‐ converts to an intact B12 cluster by successive stripping of single iodine radicals or ions.